Pengaruh Pendidikan Kewirausahaan pada Entrepreneur Behavior Index (EBI) dan Intensi Berwirausaha Mahasiswa Administrasi Bisnis - Bella Widya Septianty; Finna Fourqoniah; Muhammad Fikry Aransyah (Indonesian Journal Publisher, 2021)
This study aims to determine the effect of entrepreneurship education on EBI, the effect of entrepreneurship education on entrepreneurial intentions, the effect of EBI on entrepreneurial intentions, and the role of EBI as a mediator of influence between entrepreneurship education and entrepreneurial intentions. This research was conducted on undergraduate students of the Business Administration Study Program, Faculty of Social and Political Sciences, Mulawarman University class of 2017 and 2018. The main requirements for respondents are students who have taken entrepreneurship courses in the previous semester with a total sample of 222 people. The analysis technique uses AMOS-based SEM analysis. The results of the analysis found that entrepreneurship education has a positive and significant effect on EBI, entrepreneurship education has a positive and significant effect on entrepreneurial intentions, EBI has a positive and significant effect on entrepreneurial intentions, and EBI plays a significant role in mediating the influence of entrepreneurship education on entrepreneurial intentions. Based on the results of the research, it means that the Business Administration Study Program is able to grow and encourage students' interest in entrepreneurship which can be done through the development of entrepreneurship education curricula. And student character values ??(EBI) can be developed through experience and field practice so that they do not have to be imposed on the education.